Nutritional supplements for neuropsychiatric symptoms in people with dementia: A systematic review and meta‐analysis. (28th August 2020) - Haider, Sandra; Schwarzinger, Angela; Stefanac, Sinisa; Soysal, Pinar; Smith, Lee; Veronese, Nicola; Dorner, Thomas E.; Grabovac, Igor
Objectives: The aim of the present study was to assess the effects of nutritional supplementation on neuropsychiatric symptoms among people with dementia. Methods/Design: Randomized controlled trials (RCTs) were searched in the Databases PubMed, EMBASE, SCOPUS, Cochrane Central Register of Controlled Trials and Clinicaltrials.gov from inception until January 31, 2020. Studies of RCTs carried out on people with any type of dementia who were taking nutritional supplements and had neuropsychiatric symptoms were included in this systematic review and meta‐analysis. Neuropsychiatric symptoms were assessed with the validated Neuropsychiatric Inventory (NPI). Effect sizes were calculated with standardized mean differences (SMD) and 95% confidence intervals (95%CI), applying a random effect model. Results: The search yielded 1034 studies with four studies being included in the meta‐analysis with a total of 377 people with dementia (mean age 69.3 [SD: 7.7] years). The diagnoses comprised mild to late Alzheimer's disease and frontotemporal dementia. Two studies included a multicomponent supplementation, one an omega‐3, and one a special supplement tailored for cognitive impairment. The median follow‐up was 18 weeks, with a range from 12 to 24 weeks. Pooled data showed that nutritional supplementation did not improve NPI (SMD = −0.33; [95%CI: −0.74 to 0.08]; P = 0.11; I 2 = 45%). Conclusions: The findings of this meta‐analysis demonstrated no significant impact on NPI through nutritional supplementation. However, the generalization of the results is limited, as different supplements were used in different stages of dementia with a short follow‐up time.